(untitled) (The Journal of Psychology and Sociology, 2012)
Solving a problem of socialization in adolescence is of great signiﬁ cance not only in theoretical-methodological but also in practical aspect. An inﬂ uence of character’s accentuations upon a level of socio-psychological adaptation is represented. In modern context of globalization and integration an issue of social and psychological adaptation becomes especially actual.